2023
DOI: 10.3389/fcell.2023.1061777
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-SNAP (M105I) mutation promotes neuronal differentiation of neural stem/progenitor cells through overactivation of AMPK

Abstract: Background: The M105I point mutation in α-SNAP (Soluble N-ethylmaleimide-sensitive factor attachment protein-alpha) leads in mice to a complex phenotype known as hyh (hydrocephalus with hop gait), characterized by cortical malformation and hydrocephalus, among other neuropathological features. Studies performed by our laboratory and others support that the hyh phenotype is triggered by a primary alteration in embryonic neural stem/progenitor cells (NSPCs) that leads to a disruption of the ventricular and subve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Modulating the sorting of apical SNARE can regulate the rate of endocytosis of apical proteins, thereby affecting signal transduction and epithelial cell proliferation [ 16 , 17 ]. A study elucidated that mutations in α-SNAP could activate the AMP-activated protein kinase (AMPK) pathway in neural stem/progenitor cells, thereby diminishing cell proliferation activity [ 18 ]. Some studies have reported a correlation between α-SNAP expression and the activation of PI3K/Akt/mTORCl signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Modulating the sorting of apical SNARE can regulate the rate of endocytosis of apical proteins, thereby affecting signal transduction and epithelial cell proliferation [ 16 , 17 ]. A study elucidated that mutations in α-SNAP could activate the AMP-activated protein kinase (AMPK) pathway in neural stem/progenitor cells, thereby diminishing cell proliferation activity [ 18 ]. Some studies have reported a correlation between α-SNAP expression and the activation of PI3K/Akt/mTORCl signaling.…”
Section: Introductionmentioning
confidence: 99%